Novel approaches and strategies for biologics, vaccines, and cancer therapies - Manmohan Singh, 1964 November 8-; Salnikova, Maya (Elsevier/AP, Academic Press is an imprint of Elsevier, 2015)
Provides readers with a unique perspective on the successes and challenges that shape the development of novel biologics, vaccines and cancer therapies. This book thoroughly describes advances in the understanding of disease targets and the approaches that are developed specifically for their treatment. -- P. [4] of cover
Keywords: Pharmaceutical biotechnology; Biological Products; Neoplasms -- therapy; Technology, Pharmaceutical; Vaccines